U–Pb and Sm–Nd geochronology of amphibolites from the Curaçá Belt, São Francisco Craton, Brazil : tectonic implications - Silva, Luiz José Homem D´El-Rey (2007)
The Curaçá terrane is part of the Itabuna–Salvador–Curaçá (I–S–C) Paleoproterozoic orogen in the São Francisco craton, northeastern Brazil, and comprises supracrustal rocks, gneisses of their probable basement, amphibolites, and mafic-ultramafic Cu-bearing bodies (including the Caraíba Cu-Mine), all affected by D1-D3 deformation events associated to M1-M3 metamorphism under high-T granulite and amphibolite facies, and assisted by G1-G3 tonalitic-granodioritic-granitic intrusions. U–Pb and Sm–Nd Thermal Ionization Mass Spectrometry (TIMS) isotopic data from amphibolite, tonalite, and granite, sampled in a well-known outcrop, indicate partial reset and heterogeneous modification of the original isotopic systems, attributable to deformation and metamorphism. The ages obtained from these systems agree with each other, and also with other previously published U–Pb data, and imply that 2.6 Ga is the crystallization age of the protolith of the amphibolite. Together with key structural relationships, they also indicate a 2.08–2.05 Ga interval for M3 metamorphism, and make even a less precise age (2.2–2.3 Ga) acceptable, as it suggests contamination in the amphibolite with material in a syn-D2 tonalite crystallized 2248±36 Ma ago. The new data demonstrate the existence of Neoarchean fragments of both oceanic and continental crusts and constrain the Archean-Paleoproterozoic development of the Curaçá belt, the I–S–C orogen, and the São Francisco craton.